VET Data Report Germany 2011 : facts and analyses accompanying the Federal report on vocational education and training - selected findings - Friedrich, Michael [Herausgeber]; Hanf, Georg [Herausgeber]; Strohmaier, Eckart [Herausgeber] (Bundesinstitut für Berufsbildung, 2011)
"The Data Report accompanying the 2011 Report on Vocational Education and Training represents the third issue of this work. The first two chapters present the current situation in initial vocational training and in continuing vocational training as well as highlighting the changes which have taken place over the course of time. The main thematic focus of the 2011 Data Report is the permeability between Vocational Education and Training and Higher Education. This theme is also addressed in the fourth chapter comparing the German situation to the situation in other European countries. The chapter finishes with data on moblity as part of VET. This English version gives only a selection of the main findings." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.3.1 Ausbildung im Dualen System; S 1.5.2 Berufliche Weiterbildung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; G 1.3.3.3 Mobilität; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Ausbildungsstellenmarkt; Berufliche Weiterbildung; Durchlässigkeit im Bildungssystem; Mobilität; Indikatoren